Rancang Bangun Sistem Smart Home Berbasis Iot Untuk Monitoring Dan Pengendalian Energi Listrik - Dina Astrit Aisyah Febrianti; Ahmad Mizan; Kezia Tabita Amitakasih (CV. Multi Kreasi Media, 2025)
The Internet of Things (IoT) has become one of the most widely used technologies to support energy efficiency in households. This research presents the development of an IoT-based smart home system designed to monitor and control electricity usage in real time. The system utilizes a NodeMCU ESP8266 microcontroller integrated with current and voltage sensors to measure power consumption from household appliances. All data are transmitted via a Wi-Fi network to an IoT platform and displayed through a web-based interface, allowing users to control and monitor electrical activity remotely. The experimental results show that the system achieved up to 96% accuracy in displaying energy usage data and provided automatic alerts when the power load exceeded the set threshold. The implementation of this system improved household energy efficiency by approximately 18%, proving that IoT integration in smart homes can serve as an effective solution for smarter and more efficient electricity management.